IMPORTANCE OF LARGE ROOT SYSTEM ON INCREASING YIELD IN DRIP IRRIGATED AEROBIC RICE - T. PARTHASARATHI,; K. VANITHA,; S. MOHANDASS,; ELI VERED, (The Bioscan, 2014)
Study on the influence of drip irrigation system on certain root characters and grain yield in aerobic rice study was conducted during Dry Season (2011) in Coimbatore, India. The two lateral spacings with two discharge rate dripper treatments were experimented by using ADT(R) 45 variety. Chosen root characters were observed and correlated with the yield of aerobic rice. The increased root length, root density (length and weight), root oxidizing power, specific root length which are much favoured the yield of aerobic rice under 0.8 m lateral distance with 1.0 lph drippers. The physiological parameter of root oxidizing power improved the root activity, which was 38.2 per cent higher in 0.8 m LD with 1.0 lph dripper over the conventional aerobic rice treatment. Optimum yield (5793 Kg ha-1) was obtained in 0.8 m lateral distance, with 20x10 plant spacing along with 1.0 lph dripper treatment. Higher correlation coefficient root parameters such as Root Mass Density (0.865**), total root length (0.864**) were proved that the root system parameters were favoured the yield increment in rice under drip irrigation system. This 0.8 m lateral distance, with 20x10 plant spacing along with 1.0 lph dripper treatment might be recommended for the water scarce environment to achieve better root growth and yield in aerobic rice.